Enigmatic clusters of sandstone boulders on plateaus of the Stołowe Mountains (Sudetes, south-west Poland) – their geoheritage and geotouristic value - Migoń, Piotr; Parzóch, Krzysztof (Geologos, 2021)
Among sites of geomorphological interest in the tableland of the Stołowe Mountains, consisting of clastic sedimentary rocks of Late Cretaceous age, are enigmatic occurrences and clusters of sandstone boulders within plateau levels that are underlain by mudstones and marls. These boulders are allochthonous, having been derived from the quartz sandstone beds that support the upper plateau level and stratigraphically are in excess of 50 m above the altitudinal position of the boulders. Topographic conditions preclude long-distance transport from the escarpment slopes; boulders are hypothesised to be the last remnants of completely degraded outliers (mesas) of the upper plateau. Their present-day altitudinal position is explained by passive ‘settling’ following disintegration of caprock and denudation of the underlying weaker rocks. Two localities are here presented in detail, Łężyckie Skałki and Pustelnik, along with adjacent boulder trains in the valleys incised into the plateau. It is argued that both localities have considerable geoheritage value and both play the role of geosites, although on-site facilities are so far limited. However, the complex history of boulders sets a series of challenges for successful geo-interpretation.